Suppression of membrane fouling in the ceramic membrane bioreactor (CMBR) by minute electric field. (December 2018) - Dong, Zijun; Shang, Wentao; Dong, Wenyi; Zhao, Lingyan; Li, Mu; Wang, Rui; Sun, Feiyun
Highlights: Membrane fouling in CMBR is suppressed by applied minute electric field. Effect of the applied cathodes on fouling mitigation in CMBR was evaluated. Fe-CMBR performed lower fouling compared with Cu-CMBR and Ti-CMBR. Abstract: Three ceramic MBRs (CMBR) installed with varied electrodes, i.e. Cu, Ti and Fe, were operated in parallel under the minute electric field to evaluate their suppression effect on membrane fouling, by comparison with control CMBR. Fe-CMBR released Fe 2+ continuously to induce a higher organic removal efficiency and a smooth fouling rate. There was significant electric-flocculation effect in the Fe-CMBR, reflected by the increased sludge particle size and zeta potential, and to improve sludge filterability. Application of minute electric field could also affect the CMBR supernatant organic content and components, which was another reason for fouling mitigation. The formed membrane fouling layer was more easily to be detached by simple backwashing in all electric CMBRs, since that there were significant electric repulsive force to prevent foulants deposition.